Examining the Ability of Students to Calculate the Syllable Stress at the Second Grade SMA Negeri 2 Baubau - Ardin, Hasrida; Nurhayati, Nurhayati; Mondo, Ariamin (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
"How were the second-year students of SMA Negeri 2 Baubau ability in determining syllable-stress in the words?" was the research's problem statement. Additionally, the following were the goals of this study: to determine the second-year SMA Negeri 2 Baubau pupils' proficiency with syllable stress. The goal of this study was to assess the second-year students at SMA Negeri 2 Baubau's proficiency with syllable stress. Descriptive quantitative design was adopted in this study. The instrument utilized in this study was a question test. Purposive random sampling was employed to choose the study's sample. In order to gather data for this study, the researcher used a test that consisted of questions about stressed syllables and asked the students to respond. This was examined using percentage analysis to establish which classifications (very good, good, adequate, sufficient, and poor) the second-year SMA Negeri 2 Baubau students used to identify syllable stress in the terms. The results showed that, in terms of syllable-stress in words, the second-year students at SMA Negeri 2 Baubau scored very good, good, adequate, sufficient, and poor as follows: no student received a score of 90–100, 7 students (37%), only 9 students (47%), 8 students (42%), or sufficient, and 14 students (74%), or poor. As a result, the second-year SMA Negeri 2 Baubau students' average proficiency in identifying syllable-stress in words was adequate. Consistent with the aforementioned findings, the researcher discussed how the mean score of 58,4 suggested that the second year of SMA Negeri 2 Baubau was still challenging in determining syllable-stress in words.The majority of pupils in the sufficient achievement group of their ability to identify syllable-stress in words were unaware of stress, albeit occasionally they were.